Analysis of the protective immune response following intramuscular vaccination of calves against the intestinal parasite Cooperia oncophora. Issue 9 (August 2015) - Van Meulder, F.; Ratman, D.; Van Coppernolle, S.; Borloo, J.; Li, R.W.; Chiers, K.; Van den Broeck, W.; De Bosscher, K.; Claerebout, E.; Geldhof, P.
Graphical abstract: Highlights: Intramuscular immunisation of calves triggers an antigen-specific mucosal immune memory response. Protection was associated with antigen-specific antibody and T cell responses. Intestinal upregulation of lectins and cell adhesion molecules in vaccinated animals. Abstract: Recently we reported the successful vaccination of calves against Cooperia oncophora with a double domain activation-associated secreted protein, purified from the excretory-secretory material of adult stage parasites. In an attempt to elucidate the immune mechanisms involved in protection, the humoral and cell-mediated immune responses following vaccination and infection were compared with non-vaccinated control animals. Antigen-specific IgG1, IgG2 and IgA levels were significantly increased in sera of vaccinated animals post vaccination, whereas no effect was observed for IgM. Antigen-specific intestinal IgG1 levels were significantly increased in the vaccinated animals, whereas no differences were observed for antigen-specific IgA, IgM and IgG2 levels. Upon re-stimulation in vitro with the vaccine antigen, a significant proliferation of both αβ- and γδ-T cells, and B cells, collected from mesenteric lymph nodes, was only observed in vaccinated animals. RNA-seq analysis of intestinal tissue yielded a list of 67 genes that were differentially expressed in vaccinated animals following challenge infection, amongst which were several cell adhesion molecules, lectins and glycosyl transferases. A correlation analysis between all immunological and parasitological parameters indicated that intestinal anti-double domain activation-associated secreted protein IgG1 levels correlated negatively with cumulative faecal egg counts and positively with the proportion of L4s and L5s. The proportion of immature stages was also positively correlated with the proliferation of αβ T cells. Worm length was negatively correlated with the transcript levels of several lectins and cell adhesion molecules. Overall, the results indicate that intramuscular administration of the vaccine resulted in an immune memory response particularly characterised by increased antigen-specific IgG1 levels in the intestinal mucosa.